Implementing the Latvian Early Intervention Program (LAT-EIP) for Patients With Schizophrenia Spectrum First-Episode Psychosis: Study Protocol - Berze, Liene; Civcisa, Sandra; Krone, Ilona; Kvartalovs, Dmitrijs; Kikuste, Sarmite; Sapele, Inna; Lazovika, Jelena; Rancans, Elmars (Frontiers in Psychiatry, 2019)
Background: Patients with first-episode psychosis are mainly young people in the active phase of their social and professional lives, and psychosis is a serious disruption of normal life with high risk of disability. Integrated biopsychosocial early intervention treatment is crucial for patients with first-time psychosis episode. The purpose of this trial is to adapt the first early intervention program for patients with first-time non-affective psychosis in Latvia, and to investigate whether it is possible to integrate this kind of treatment approach in the frame of existing services and whether it provides better outcomes for patients than existing services. Design/Methods: The study has a nonrandomized controlled design in a real-life environment. Participants are all consecutive patients presenting in the psychiatric emergency room with first-time non-affective schizophrenia spectrum psychosis episode (ICD criteria F23, F20) from a catchment area of 262,541 inhabitants, with urban and rural regions. The Latvian Early Intervention Program is a 6-month program developed from existing treatment guidelines and recommendations and adapted to a low-resource environment, integrated in an existing outpatient unit. This study aimed to test the hypothesis that the patients who received intervention have milder symptoms, higher functioning, and better adherence to outpatient treatment. The study primary aims are: 1) to establish and examine in practice the adapted early intervention for patients with first schizophrenia spectrum psychosis; 2) compare clinical and functional outcomes (including occupation, housing, and social relationships) between intervention treatment and standard treatment; and 3) compare the number of rehospitalizations, adherence to outpatient treatment, and assigned disability. Secondary aims are: 1) to compare full recovery status in both treatment groups at 12 months follow-up and 2) to develop recommendations for establishing early intervention programs in limited resource settings. Discussion/Conclusions: Across the world, there is wide inequality in the availably and accessibility to early intervention treatment. This study will increase our knowledge in early intervention treatment approach and outcomes for patients with schizophrenia spectrum first psychosis episode in real-life working clinical practices. We hope to provide theoretical and practical aspects to develop strategies for early intervention service implementation in limited resource mental healthcare settings.